Left-Handedness and Economic Development - Fabio Mariani; Marion Mercier; Luca Pensieroso (Institute of Labor Economics (IZA), 2021)
This paper studies the interplay between left-handedness and economic development. To explain the decline and subsequent recovery of left-handedness observed over the last few centuries in the Western world, we propose a theory in which economic development influences the prevalence of left-handedness through structural change and a genetic mechanism driven by differential fertility. We further explore the possibility that the prevalence of left-handedness influences growth, finding that the link between handedness and economic performance varies across stages of development. Consistent with the implications of our model, the analysis of US data suggests that left-handedness can positively contribute to growth, once the economy has reached a sufficiently high level of human capital. Our research provides an example of how economic development can shape evolutionary forces, thus improving our understanding of the growth-diversity link.
Keywords: O11; O14; O33; O40; J13; J24; Q57; 330; handedness; economic growth; evolution; diversity; unified growth theory